Fenestrated endovascular repair of aortic arch aneurysm in patients with bovine arch using the Najuta stent graft - Toya, Naoki (J Vasc Surg Cases Innov Tech, 2018)
We describe the case of a 74-year-old man with a thoracic aortic aneurysm with a bovine arch who underwent fenestrated endovascular repair of aortic arch aneurysm using the Najuta stent graft (Kawasumi Laboratories, Inc, Tokyo, Japan). He has had a previous endovascular aneurysm repair and femoropopliteal bypass for abdominal aortic aneurysm combined with peripheral arterial disease. The Najuta stent graft was inserted and deployed at zone 0 with delicate positional adjustment of the fenestration of the stent graft to the brachiocephalic trunk. There was no endoleak or complication. His postoperative course was uneventful. At 7-month follow-up, complete exclusion of the aneurysm was noted. The Najuta stent graft repair of aortic arch aneurysms is a safe and effective treatment option for patients with a bovine arch.